Ecogeomorphology of Zilaki and Disum Rivers by Emphasis on Dissolution Load - Behzad, Ardavan; Sarvati, Mohammad Reza; Moghimi, Ebrahim (International Journal of Bio-resource and Stress Management, 2012)
The geomorphic parameters are the most important and effective factors on the ecological quality of the rivers. The physical and chemical quality of the rivers water can be due to lithology of the formation existing in the water field, the sediments delivered to the river and the biological factors. In this study, the effects of parameters affecting the chemical quality of the water of the two rivers of Zilaki and Disum have been examined. The expansion of calcareous formation in the upstream of the field of these rivers, much rains, forest coverage and water branches and the entrance of water drainage resulted from cultivation of rice in the spring season is influential on the solvent salts of the river water and in the regions that the morphology of the river had a flat surface and condition has not caused a negative effect on the ecology of the river. By using the hydrometric stations available on the water of these rivers, the quality statistic of their water was obtained in three sections of minimum, medium and maximum and the Water Quality software was used to analyze it. The results which were provided from the salts of different solvents of water in the rivers of Zilaki and Disum indicate that under the ordinary situation, the geological factors and geomorphology did not have a negative effect on the quality of the water and by interference of ecological factors such as the entrance of water drainage resulted from agriculture in the spring causes that the salts of the water to be approximately increased which had the most impact on electrical conductivity of these rivers.